The Value of local wisdom in developing indigenous counseling - Lestari, Indah; Mahfud, Ashari; Mulawarman, Mulawarman (FKIP Universitas Lampung, 2020)
The Value of Local Wisdom in Developing Indigenous Counseling. Objectives: This study aims to obtain a critical analysis of local culture-based counseling with a systematic review as a method. Method: This research uses an article search engine sourced from a database; spinger, sagepub and doaj. Literature review found 5 journals related to indigenous culture and cultural therapy with a qualitative approach. Based on the criteria of inclusion and exclusion as a material consideration in selecting articles. Finding: The results obtained indicate that culture provides an important meaning in the counseling process, because counseling is basically a cultural gathering. To understand culture, therapists need to understand what is normative in that cultural group. Conclusion: By understanding the cultural aspects of each individual, it is possible to design approaches that accommodate the power of culture with counseling theories that are adaptive to the culture in which counseling is practiced. Keywords: local wisdom, counseling, literature review. DOI: http://dx.doi.org/10.23960/jpp.v10.i3.202002